Effect of Annealing Temperature on the Morphology and Piezoresponse Characterisation of Poly(vinylidene fluoride-trifluoroethylene) Films via Scanning Probe Microscopy - K. Lau; Y. Liu; H. Chen; R. L. Withers (Advances in Condensed Matter Physics)
Poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE (70/30)) films were synthesized on a gold/glass substrate via spin coating. The films were annealed at a temperature between 125∘C and 180∘C. Nanoscale characterisation of the morphology, polarization switching, and local piezoresponse hysteresis loops of PVDF-TrFE film was studied using a scanning probe microscope (SPM). Ferroelectric switchable domains were identified by piezoresponse force microscopy (PFM) for all films. Small grains, with weak piezoresponse character, were observed for films annealed just above the Curie temperature. Acicular grains were obtained when the annealing temperature approached the melting point and the piezoresponse increased. Annealing above the melting point decreased the piezoresponse and the morphology changed dramatically into plate-like structures.